2021
DOI: 10.1080/2162402x.2021.1969767
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of infiltrating B cells and tertiary lymphoid structures in the TME of gastric adenocarcinomas

Abstract: The occurrence and development of gastric adenocarcinoma (gADC) is closely related to the interaction between tumor cells and immune cells in the tumor microenvironment (TME). Our objective was to characterize the repertoire of immune cells in the TME of gADC. To analyze the transcriptomic, immune, and spatial information of TME in gADC, we constructed single-cell RNA sequencing, 10 × Genomics V(D)J analysis, multiple immunofluorescence techniques, and OSCmap analysis of 49,765 single cells in seven samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
(42 reference statements)
4
23
0
Order By: Relevance
“…Recently, the development of single-cell sequencing technology has enabled the analysis of tumor microenvironmental components at a higher resolution ( 35 , 36 ). A variety of cell subpopulations have been identified in GC, and these subpopulations exhibit completely different biological and immunological functions, thus revealing the high complexity of the microenvironment ( 37 , 38 ). In addition, studies on a variety of tumors have also suggested that different types of cancer may have similar immune cell types, but their proportions are different ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of single-cell sequencing technology has enabled the analysis of tumor microenvironmental components at a higher resolution ( 35 , 36 ). A variety of cell subpopulations have been identified in GC, and these subpopulations exhibit completely different biological and immunological functions, thus revealing the high complexity of the microenvironment ( 37 , 38 ). In addition, studies on a variety of tumors have also suggested that different types of cancer may have similar immune cell types, but their proportions are different ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…ScRNAseq analysis by Li et al (2022) reveals T cells as the most highly enriched immune cell population in the tumor microenvironment (TME), and their ratio increases as the disease advances (24). A greater diversity of unique T cell subsets and T cell receptor (TCR) repertoire were identified within tumor tissues when compared with that of patient-matched healthy tissue or peripheral blood mononuclear cells (PBMCs), suggesting that a variety of unique T cells infiltrate the TME (22). The main subsets of T cells that show infiltration into the TME in gastric cancer scRNAseq datasets include CD4 + T helper cells (Th, co-expressing CD4), CD8 + cytotoxic T lymphocytes (CTL, coexpressing CD8A), regulatory T cells (Treg, co-expressing FOXP3), and natural killer T cells (NKT, co-expressing NKG7) (20,22,26,39).…”
Section: T Cellsmentioning
confidence: 99%
“…A greater diversity of unique T cell subsets and T cell receptor (TCR) repertoire were identified within tumor tissues when compared with that of patient-matched healthy tissue or peripheral blood mononuclear cells (PBMCs), suggesting that a variety of unique T cells infiltrate the TME (22). The main subsets of T cells that show infiltration into the TME in gastric cancer scRNAseq datasets include CD4 + T helper cells (Th, co-expressing CD4), CD8 + cytotoxic T lymphocytes (CTL, coexpressing CD8A), regulatory T cells (Treg, co-expressing FOXP3), and natural killer T cells (NKT, co-expressing NKG7) (20,22,26,39). Among these infiltrated subsets, some T cells have been implicated in a tumor-promoting role and others in a tumorinhibiting role.…”
Section: T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…GC development undergoes a multi-stage process, from no-atrophic-gastritis (NAG) to chronic atrophic gastritis (CAG) to intestinal metaplasia (IM), and finally GC ( 2 ). During this process, gastric mucosa tissue and the tissue microenvironment (TME) undergo dynamic changes ( 3 ). The TME includes a variety of cell types (immune cells, fibroblasts, endothelial, etc.)…”
Section: Introductionmentioning
confidence: 99%